Pelatihan Mindfulness Based Cognitive Therapy bagi Guru Bimbingan dan Konseling untuk Mereduksi Kecanduan Judi Online dan Agresivitas Remaja - Zadrian Ardi; Ilmiyati Rahmy Jasril; Anindra Guspa; Frischa Meivilona Yendi; Ade Herdian Putra (Universitas Negeri Padang, 2025)
Online counseling training based on Mindfulness-Based Cognitive Therapy (MBCT) for guidance and counseling teachers was conducted in response to the increasing phenomenon of online gambling addiction and aggressive behavior among adolescents. This phenomenon has become a serious concern in Payakumbuh City because it affects students' academic, psychological, and social aspects. This Community Service Program aims to improve the capacity of guidance and counseling teachers in understanding, internalizing, and applying the MBCT approach in school counseling services. The training was held on August 9, 2025, at the Payakumbuh City Education Office Hall, involving guidance and counseling teachers from various schools. The implementation method consisted of two stages, namely an introduction to online counseling for online gambling addiction and aggressive behavior in adolescents, as well as training in MBCT techniques through practical simulations and group discussions. Evaluation was carried out using pre-test and post-test instruments to measure participants' understanding and skills. The training results showed an increase in understanding from 52 percent to 91 percent and in skills from 48 percent to 88 percent. Participants also developed plans to implement MBCT in their respective schools and built a collaborative network among guidance counselors. These findings indicate that participatory training combining theory and practice is effective in strengthening the professional competence of guidance counselors. The MBCT approach is considered relevant as a strategy for preventing and intervening in risky adolescent behavior, especially when combined with online counseling technology that expands access to services in schools.